2017
DOI: 10.22146/ijg.11315
|View full text |Cite
|
Sign up to set email alerts
|

The Political Geography of Voters and Political Participation: Evidence from Local Election in Suburban Indonesia

Abstract: The praxis of political issue including voter turnout and political participation does not exist in a vacuum. Therefore, geographical and spatial issues are frequently engaged and even embedded into it. Thus, this article is written with one purpose: to investigate the spatial relationship of voter turnout and their political participation. As stated earlier, the complexity of the political analysis based on geography will take us on a multidimensional approach that includes social, cultural and economy. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Gimpel et al (2004) studied abstentionist voting in counties in the United States during the 2000 presidential elections and showed that the geographic context affects voter turnout, highlighting neighborhood effects between counties. Yandri (2017) reached a similar conclusion from an analysis of local elections in peri-urban areas in Indonesia which showed that there is a spatial autocorrelation of non-voters in peripheral and peri-urban areas. These theoretical arguments and empirical results justify the need to take these neighborhood effects into account.…”
Section: Methodology and Datasupporting
confidence: 52%
“…Gimpel et al (2004) studied abstentionist voting in counties in the United States during the 2000 presidential elections and showed that the geographic context affects voter turnout, highlighting neighborhood effects between counties. Yandri (2017) reached a similar conclusion from an analysis of local elections in peri-urban areas in Indonesia which showed that there is a spatial autocorrelation of non-voters in peripheral and peri-urban areas. These theoretical arguments and empirical results justify the need to take these neighborhood effects into account.…”
Section: Methodology and Datasupporting
confidence: 52%
“…The emergence of residential areas precisely resulted in the low political participation of its citizens (Schram, 1991). The study of the situation was verified by Newman et al (2013) in the United States and (Yandri, 2017) in South Tangerang Municipality, Indonesia. All such information implies that residential areas should apply sustainability principles.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Politically, the growth of suburban areas, one of which is marked by the emergence of the residential real estate and/or housing clusters, resulted in a low level of political participation by citizens because of a situation referred to as gentrification (Schram, 1991). A study of the situation was verified by studies conducted Newman, et al (2013) in the United States and Yandri (2017) in the city of South Tangerang, Indonesia.…”
Section: Introductionmentioning
confidence: 96%